Physical and chemical characterization of building materials - Pérez-Martínez, Manuel; Dueñas-Buey, Mª Concepción; Gordo Puertas, Elisa; León-Reina, Laura; Liger-Pérez, Esperanza; González Montero, Rocío; Cabello Ganuza, María; Ruiz-Cruces, Rafael; Cañete-Hidalgo, Sergio Andrés (My University, 2017)
The products used in the construction of buildings and infrastructures, are made from raw material extracted directly from nature, and after suitable transformation processes are placed on site. Approximately 2.5 tons of materials per square meter are used in a residential building. The most abundant percentages are: Gravel and sand 57.8, ceramics 21.6, cement 12.5, lime 1.98 and gypsum 0.46. Some materials used cause a high impact of negative character in the environment but their quantification is low whereas others of low impact but are used of massive form in construction reason why they can cause serious hazards for the human health. The raw material used in the manufacture of construction materials is extracted directly from nature or is originated by a mixture of raw material and recycled material. In any case, it is necessary to analyze the chemical composition of the construction products whether they are natural, whether they are transformed or mixed. The purpose of this work was to perform a physical-chemical characterization of samples from factories located in three regions of different geological nature: granitic, calcareous and sedimentary. The materials analyzed come from different factories located in Spain 18 factories of cements, bricks and tiles 15, ceramics 16, sands 15 and natural stones 18. They were supplied by manufacturers and it has been made a physic-chemical characterization of the samples received. The chemical composition of the samples of cement, brick, ceramic and roofing tile has been made using ICP-MS and EDXRF. The results of these analyze shows near 72 different elements. The higher concentrations are of Na, K, Ca, Al, Fe and Si. All the samples were also characterized using XRPD. It is a powerful tool for material characterization in general, and cements materials in particular. The use of the Rietveld method has allowed quantifying the clinkers and cements measured by laboratory x-ray powder diffraction (LXRPD) giving their accurate phase assemblage. From the average composition of the different classes of cements analyzed, it is concluded that, except for two samples, the rest all correspond to Portland cements of different strength.
Keywords: Materiales de construcción; Building materials; ICP-MS; EDXRF; Radiactivity; XRED